RESTORING CUSTOMARY FOREST RIGHTS THROUGH AGRARIAN REFORM: CASE STUDY OF THE KAMPAR COMMUNITY, INDONESIA - Fikri, Mhd Zakiul (Fakultas Hukum, Universitas Diponegoro, 2024)
Approximately three-quarters of Kampar Regency is designated as state forest, despite the historical presence of indigenous communities for generations. Accordingly, this study examines on analyzing the framework for restoring the customary forest rights of these through agrarian reform, emphasizing social forestry. Employing a socio-legal research method, the study combines textual analysis of legal frameworks and case studies of Kampar's indigenous communities. The research examines two key issues: (1) the presence of indigenous communities and the concept of customary forest utilization in Kampar Regency, and (2) the importance of restoring indigenous communities’ rights to forests through social forestry initiatives. The findings reveal that indigenous communities in Kampar Regency maintain a strong connection to their ancestral heritage, viewing customary forest as inalienable heritage. The restoration of indigenous communities’ rights to these forest territories is considered essential. Social forestry is identified as a critical component of agrarian reform in Indonesia, with existing regulatory frameworks explicitly acknowledging indigenous communities as beneficiaries. Several areas of customary forest in Kampar Regency have also been identified as having potential for designation through social forestry programs.